Lissencephaly Type I: A case report - Aydınoğlu, A.hakan; Güngör, Serdal; Yıldırım, Hanefi; Gürgöze, Metin K. (Fırat University, 2001)
Neuronal migration disorders are a group of malformations of the brain which primarily affect development of the cerebral cortex. Type 1 lissencephaly, the most common form of the neuronal migration disorders, is characterized by a flattened and thickened cerebral cortex with absent or reduced cortical gyri. Type 1 lissencephaly may manifest by variable clinical findings. A 4-years-old girl with convulsion and psychomotor retardation who was diagnosed to have agyria-pachygyria by magnetic resonance imaging was reported for rarely occurence.

Nöronal migrasyon bozuklukları primer olarak serebral korteksin gelişimini etkileyen bir grup malformasyondur. Nöronal migrasyon bozukluklarının en sık şekli olan tip 1 lisensefali kortikal girusların azalması ya da yokluğu ve serebral korteksin yassılaşması ve kalınlaşması ile karakterizedir. Tip 1 lisensefali değişik klinik bulgularla ortaya çıkabilir. Burada motor-mental geriliği ve konvülziyonu olan ve kraniyal manyetik rezonans görüntülemede agiri-pakigri saptanan 4 yaşındaki kız olgu nadir görülmesi nedeni ile sunuldu.
LİSENSEFALİ TİP 1: OLGU SUNUMU